PENINGKATAN HASIL BELAJAR PAI MELALUI PENGGUNAAN MEDIA AUDIO VISUAL DI KELAS IV SD NEGERI KARANGGINTUNG 02 KECAMATAN GANDRUNGMANGU KABUPATEN CILACAP - Nurlaeli, Siti; Nur, Muhamad Amin; Mujtahid, Mujtahid (Muta'allim: Jurnal Pendidikan Agama Islam, 2023)
Researchers are interested in using audio-visual media to improve student learning outcomes. The problem raised in this research is whether the use of audio visual media can improve student learning outcomes in PAI subjects in Class IV of SD Negeri Karanggintung 02, Gandrungmangu District. This research uses a classroom action research design. This research procedure consisted of two learning cycles. Data collection techniques were carried out using test and observation techniques. Data analysis uses qualitative descriptive analysis techniques and descriptive statistical analysis. The results of this research reveal that the use of audio-visual media can improve student learning outcomes in PAI subjects in class IV of SD Negeri Karanggintung 02, Gandrungmangu District. This is based on the results of learning evaluations which show an increase in student learning outcomes from one cycle to the next. Before implementing the action, the average student score was 69.25 with a completion percentage of 70%, but after implementing the action in cycle I the average student score increased to 74.40 and the percentage of learning completion also increased to 85% of all students. In cycle II the students' average score was 76.50 and the percentage of learning completion reached 100%. This achievement has exceeded the research performance indicator, namely